2008
DOI: 10.1530/eje-07-0877
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hyperthyroidism in Stockholm, Sweden, 2003–2005.

Abstract: Objectives: To investigate the incidence of hyperthyroidism in Stockholm County, in those patients who were diagnosed with hyperthyroidism for the first time during the years 2003-2005. Design: All new cases of hyperthyroidism R18 years of age were prospectively registered to calculate the total incidence of hyperthyroidism, as well as the incidence of the subgroups: Graves' disease (GD), toxic multinodular goitre and solitary toxic adenoma (STA). Eight specialized units/hospitals in Stockholm County participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…This study is strengthened by the recruitment method that ensures that patients from every clinic in a defined area and population would be recorded. Although this was not an epidemiological study, the incidence was in accordance with previous Swedish incidence studies (34,35,36). Thus, we probably have included almost all eligible subjects and only a small proportion of the patients chose to opt-out from participation.…”
Section: Discussionmentioning
confidence: 71%
“…This study is strengthened by the recruitment method that ensures that patients from every clinic in a defined area and population would be recorded. Although this was not an epidemiological study, the incidence was in accordance with previous Swedish incidence studies (34,35,36). Thus, we probably have included almost all eligible subjects and only a small proportion of the patients chose to opt-out from participation.…”
Section: Discussionmentioning
confidence: 71%
“…The incidence of MNTG in Denmark (34.6 per 100 000 person-years) is higher than in most other countries studied, where the calculated SIRs spanned from 3.3 to 30.5 per 100 000 person-years (6,8). All these studies were performed in regions with a higher iodine intake in the population compared with Denmark.…”
Section: Subtypes Of Hyperthyroidismmentioning
confidence: 96%
“…Many studies not only included patients with biochemical overt hyperthyroidism, but also patients with subclinical hyperthyroidism (7), or may have identified patients by means of biochemical screening (2). Other studies only evaluated certain age groups (8). Most studies were based on patients referred to hospital departments (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), potentially leading to referral bias (19).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of thyrotoxicosis has previously been determined in Sweden and studies showed a variation between 25.8 and 43.0 cases per 100 000 per year (1)(2)(3)(4). In other studies in Europe, outside Sweden, performed in Iceland, Denmark, and the UK the incidence varied between 9.7 and 56.5 per 100 000 and year (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 94%